Penerapan Metode Flash dalam Hafalan Juz ‘Amma untuk Anak Usia Dini - Nur Hidayat (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to describe the application of the flash method in memorizing juz 'Amma which is applied at the House of tahfidz Qur'an 'Aisyiah Nganjuk city. This research uses a descriptive method with a qualitative approach. The research subject is the teacher of the children's tahfidz program and the research informants include the head of the institution, as well as students and parents of students. Data collection uses observation, interview and documentation methods. The results of this study found data that, the method used in memorizing juz 'amma is the flash method. Supporting factors in the application of this method are professional mentor teachers, conducive rooms and interesting media. The inhibiting factors are playing, absence due to illness and parents' busyness. The efforts made by the institution in achieving program success are the existence of a student progress report book to become a reference for parents in muroja'ah at home, the existence of parent meetings for each class to be given motivation and direction and the existence of monthly meetings to learn together in the form of fun activities.